2015
DOI: 10.1017/s0033291715001129
|View full text |Cite
|
Sign up to set email alerts
|

Combined social cognitive and neurocognitive rehabilitation strategies in schizophrenia: neuropsychological and psychopathological influences on Theory of Mind improvement

Abstract: Background. Neurocognitive and social cognitive impairments represent important treatment targets in schizophrenia, as they are significant predictors of functional outcome. Different rehabilitative interventions have recently been developed, addressing both cognitive and psychosocial domains. Although promising, results are still heterogeneous and predictors of treatment outcome are not yet identified. In this study we evaluated the efficacy of two newly developed social cognitive interventions, respectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 44 publications
3
34
1
Order By: Relevance
“…Generally speaking, our study found positive results similar to other recently published integrative approaches, 9,12,14 including the previous trial with the first version of REHACOP. 13 Unfortunately, direct comparisons with these previous results with REHACOP are very difficult. The main reasons are different clinical profile of the patients, the different duration of both versions of the intervention, and differences between outcome measures (UPSA versus WHO-DAS).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Generally speaking, our study found positive results similar to other recently published integrative approaches, 9,12,14 including the previous trial with the first version of REHACOP. 13 Unfortunately, direct comparisons with these previous results with REHACOP are very difficult. The main reasons are different clinical profile of the patients, the different duration of both versions of the intervention, and differences between outcome measures (UPSA versus WHO-DAS).…”
Section: Discussionmentioning
confidence: 96%
“…More recently, some authors combined cognitive remediation with social cognitive remediation 9,12,13 obtaining better results than patients receiving cognitive remediation alone in several domains. There is additional evidence that the combination of different trainings reciprocally boosts the effects of the treatments.…”
Section: Introductionmentioning
confidence: 99%
“…All enrolled patients underwent 6 months of rehabilitation, including both computer‐assisted cognitive remediation therapy and standard rehabilitation therapy, detailed in previous studies . Of the 104 enrolled patients, 58 patients were treated also with sociocognitive rehabilitation programs that have been previously demonstrated to improve theory of mind (ToM) and are described in detail in previous studies . After these interventions, patients were followed naturalistically in different settings, mainly at the clinic as outpatients.…”
Section: Methodsmentioning
confidence: 99%
“…Bechi and colleagues (168) showed that combination of CRT and social cognitive or ToM training improved social cognitive abilities even further than CRT alone in people with schizophrenia (168). ToM training involves reading comic strips to be trained to recognize relevant details and collect and meaningful pieces of information such as place, time, characters' actions, and physical features.…”
Section: Targeting Social Cognition Deficitsmentioning
confidence: 99%